The homes from hell? Media perceptions of residential child care - Anne Clackson; Sheryl Lindsay; Alan MacQuarrie (Scottish Journal of Residential Child Care)
Since spring 2001 library staff of the Scottish Institute for Residential Child Care have monitored over thirty online newspapers and news services for stories in which some aspect of residential care has been featured. This paper looks at the online newspapers surveyed during the six month period of July 2001 to December 2001. The articles were categorised into into five broad categories: child abuse and neglect; absconding; education; staffing and training; and legal and policy issues. Articles were then evaluated in terms of positive, negative or factual tone. This paper highlights some of the problematic issues which can be raised in press reporting using analysis of the findings and to case examples.